1987
DOI: 10.1128/jb.169.10.4804-4810.1987
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of an unstable argG gene to a 5.7-kilobase amplifiable DNA sequence in Streptomyces lividans 66

Abstract: The relationship between an unstable argG gene and a 5.7-kilobase (kb) (Camr) and that together these genes may be located in a silent chromosomal arc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 35 publications
(41 reference statements)
1
26
0
Order By: Relevance
“…For example, those in S. glaucescens can be 800 kb or more long (11), and in S. ambofaciens, PFGE analysis has revealed deletions of up to 2 Mb of contiguous DNA (57). In S. lividans and S. coelicolor, frequent deletions at least 40 kb long include the argG locus and a determinant of chloramphenicol resistance (8,29); these genes were located, by recombination analysis, near to 3 o'clock in S. lividans (8).…”
Section: Methodsmentioning
confidence: 99%
“…For example, those in S. glaucescens can be 800 kb or more long (11), and in S. ambofaciens, PFGE analysis has revealed deletions of up to 2 Mb of contiguous DNA (57). In S. lividans and S. coelicolor, frequent deletions at least 40 kb long include the argG locus and a determinant of chloramphenicol resistance (8,29); these genes were located, by recombination analysis, near to 3 o'clock in S. lividans (8).…”
Section: Methodsmentioning
confidence: 99%
“…141 "C alone or after mixing with authentic 1,3-diacetoxychloramphenicol. and JGlO had an MIC of 20 pg ml-l but strains M417 and M252, both of which had been selected for sensitivity to chloramphenicol (Betzler et al, 1987;Schottel et al, 198 l), failed to grow at drug concentrations above 3 and 6 pg ml-l, respectively.…”
Section: Analysis Of Culturesmentioning
confidence: 99%
“…Several groups were, however, able to demonstrate a chromosomal location for genes coding for certain unstable traits (6,11,12), including strS and melC from S. glaucescens. Interestingly, in this species the resulting genetic map (20) could not easily be reconciled with subsequently obtained physical linkage data, which clearly showed that the two loci are 350 kb apart (7).…”
Section: Genetic Instabilitymentioning
confidence: 99%
“…22,23,28). Additionally, analyses involving DNA surrounding unstable genes demonstrated that extensive flanking sequences were also absent, implicating large chromosomal deletion events in the instabilities (6,7,18). In S. glaucescens, deletions which were responsible for the loss of the unstable genes coding for tyrosinase (melC) and hydroxystreptomycin phosphotransferase (strS) were initially characterized (22,23).…”
Section: Chromosomal Deletionmentioning
confidence: 99%
See 1 more Smart Citation